An analytical study of some of the deterministic variables of the stage of advancement and its relation to the accuracy of the performance of the skill of high jump correction - م.م. سكنة عبد الرزاق طارش أ.دبشرى كاظم أ.د. انتصار كاظم (الرياضة المعاصرة, 2018)
Introduction, importance and problem of researchthe researcher dealt with the game of handball in general and the skill of jumping high, "in particular, which is an important offensive skills in the handball game and the most important types of correction and most used," This is what most of the specialists and the operators of the training because it is more influential " Accuracy in performance.